2008 the 19th IEEE/IFIP International Symposium on Rapid System Prototyping 2008
DOI: 10.1109/rsp.2008.32
|View full text |Cite
|
Sign up to set email alerts
|

Functional DIF for Rapid Prototyping

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
89
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 15 publications
(17 reference statements)
0
89
0
Order By: Relevance
“…This deterministic special case of EIDF is called core functional dataflow (CFDF) [20], and is the basis for a major component of the capability in DIF for modeling dynamic signal processing applications. Although CFDF is significantly restricted compared to EIDF, it is highly expressive as a deterministic dataflow model of computation.…”
Section: Enable-invoke Dataflowmentioning
confidence: 99%
See 2 more Smart Citations
“…This deterministic special case of EIDF is called core functional dataflow (CFDF) [20], and is the basis for a major component of the capability in DIF for modeling dynamic signal processing applications. Although CFDF is significantly restricted compared to EIDF, it is highly expressive as a deterministic dataflow model of computation.…”
Section: Enable-invoke Dataflowmentioning
confidence: 99%
“…Although CFDF is significantly restricted compared to EIDF, it is highly expressive as a deterministic dataflow model of computation. Indeed, it has been shown that Boolean dataflow actors [4] can be transformed into functionally equivalent CFDF actors [20]. From such a transformation and the established Turing completeness of Boolean dataflow, it can be demonstrated that CFDF is also Turing complete.…”
Section: Enable-invoke Dataflowmentioning
confidence: 99%
See 1 more Smart Citation
“…Core functional dataflow (CFDF) is a deterministic sub-class of enable-invoke dataflow (EIDF) [15] in which dynamic functionality in an actor is specified as a set of actor modes. In each mode, the actor possesses deterministic dataflow behavior, meaning that the production/consumption rates on all actor output/input ports are known, constant values.…”
Section: Introductionmentioning
confidence: 99%
“…To express dynamics in complex signal processing applications, a number of dynamic dataflow models have been proposed, including parameterized synchronous dataflow (PSDF) [2], Boolean dataflow (BDF) [7], and core functional dataflow (CFDF) [15]. PSDF provides semantics to manipulate application parameters in dataflow models at run-time.…”
mentioning
confidence: 99%